Effect of Fermented Lime Waste Flour on the pH of the Small Intestine and Microbes of Broiler Chicken Ileum - H. D. Shihah; D. Sunarti; S. Sumarsih (Universitas Bengkulu, 2021)
The balancing of digestive tract microbe can improve the digestive health of broiler chickens. Fermented lime waste flour (FLWF) contains citric acid, which can decrease digestive tract pH value to suppress pathogenic bacteria development and improve lactic acid bacteria growth in the small intestine of the broiler. The purpose of the study was to evaluate the effect of using FLWF on pH value and small intestine microbial of broiler chickens. This study used 200 female broiler chickens. The research used a completely randomized design with four treatment levels of FLWF by 0%, 1%, 2%, and 3% in every ration, with each treatment replicated five times. The parameters observed are the pH value of the small intestine, lactic acid bacteria ileum, and Coliform ileum. Data were calculated using the analysis of variance and difference test with Duncan's Multiple Range Test using the SPSS 19.0 program. The result indicates that using FLWF decreased (p<0.05) Coliform in the ileum, while pH value of small intestine and ileum lactic acid bacteria among treatments were not influenced (p>0.05). It concludes that adding FLWF at a 1% level could decrease ileum Coliform. Still, it could not decrease the pH value of the small intestine and increase the total lactic bacteria ileum.